Komunikasi Transendental dalam Yoga - Dewi, Putu Ayu Sri Kumala; Puasa, I Made Gde (Institut Hindu Dharma Negeri Denpasar, 2020)
Transcendental communication means communication between humans and their God and entering into the field of religion, participants in transcendental communication are humans with their Lord. But the discussion is little in the discipline of communication, even though this is more important than other forms of communication, especially in people who believe in the existence of God. This transcendental communication in Hinduism can be seen in a yoga activity. Yoga is an activity that aims to get closer to God. Yoga is done by uniting the mind, body, and soul with the aim of uniting oneself with God itself can be a unique study in transcendental communication. This article aims to discuss why yoga can be said to be a process of transcendental communication and the process of transcendental communication that occurs in yoga. This article uses the theory of symbolic interactionism as a scalpel in studying both problem statements. As for the results of the discussion of this article that by realizing the meaning of awareness of the meaning and motives of individuals, yoga practitioners carry out a discipline of awareness about cognitive focus and calm to minimize mental imbalances so that ultimately able to create an individual transformation and communication of mental transfiguration between individuals with God that is in the individual itself. The process of transcendental communication takes place in yoga activities because a yogi is aware of the existence of God and with the aim to get closer and unite his mind, body and soul with God himself.